Going to the hospital - Civardi, Anne; Bates, Michelle; Cartwright, Stephen; Francis, Neil (London Usborne, 2005)
This series introduces young children, in an amusing and friendly way, to situations they might find themselves in for the first time
English Stories
Keywords: English stories